Conceptual Construction of a Water Resource Recovery and Purification System Based on an Artificial Intelligence Management Model - Chang , Hung-Li; Keng, Ching-Jui; Liu, Yu-Lun; Jiang, Han-Ling (Management Analytics and Social Insights, 2024)
Given the trends of energy shortages, sustainability demands, and increased awareness, along with operational challenges in water utilities, there are new opportunities for the future of water treatment. Unfortunately, current wastewater treatment systems and technologies lack integration and a comprehensive management model. This conceptual paper proposes planning and implementing a wastewater treatment system designed to enhance efficiency and reduce operating costs. It emphasizes proactive measures to ensure stable operation and aims to achieve intelligent management of wastewater treatment, guiding the industry towards more efficient and environmentally friendly practices.